Effects of train speed and passenger capacity on the environmental vibration of viaduct and surrounding soil of suburban railways - Hongkai Wang; Dong Li; Jili Yin; Zhimin Li; Zhoujian You; Futong Wang (Scientific Reports)
Abstract Compared with the general urban rail transit, some of the current rapid urban rail transit can reach a maximum speed of 140 km/h when the train is running, which exceeds the speed level of the general urban rail transit. To consider the influence of different speeds and loads on the vibration of viaducts and the surrounding soil environment, this paper establishes a three-dimensional finite element model of rail-viaduct soil. The results show that: the frequency domain acceleration of each measurement point increases with the increase of train speed; except for the measurement point which is 20 m away from the centerline of the track, the frequency domain speed of each measurement point increases with the increase of train speed; the frequency domain speed under the low-frequency component of the viaduct measurement point increases with the increase of train loading, and the growth rate is obviously larger than that of the middle and high frequency bands, and the frequency domain speed of the measurement points in the site also increases with the increase of train loading, and the growth rate of the low-frequency band is obviously larger than that of the middle and high frequency bands. The frequency domain velocity at each measurement point of the site also increases with the increase of train load, and the growth rate of the low-frequency band is obviously larger than that of the middle and high-frequency bands.